2020
DOI: 10.1371/journal.pone.0228498
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vibrant Soundbridge on tinnitus accompanied by sensorineural hearing loss

Abstract: Objectives Tinnitus is a common symptom among patients with hearing loss, and many studies have reported successful tinnitus suppression with hearing devices. Active middle ear implantation of the Vibrant Soundbridge (VSB) is a good alternative to existing hearing devices. This study evaluated the effects of VSB implantation on tinnitus and sought to identify the main audiological factor that affects tinnitus suppression. Methods The study participants were 16 adults who had tinnitus with sensorineural hearing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…At the same time, 73 % of the VSB patients reported a reduction of their depression which was evaluated by means of the Beck Depression Inventory (BDI) and a reduced stress perception was shown in 55 % of the patients by the Brief Encounter Psychosocial Instrument (BEPSI). A Korean research team revealed a significant reduction of the tinnitus perception by means of the THI in 16 patients treated with VSB [119]. Marino et al also analyzed the impact of VSB on existing tinnitus in 10 treated patients [120].…”
Section: Effect On Tinnitusmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, 73 % of the VSB patients reported a reduction of their depression which was evaluated by means of the Beck Depression Inventory (BDI) and a reduced stress perception was shown in 55 % of the patients by the Brief Encounter Psychosocial Instrument (BEPSI). A Korean research team revealed a significant reduction of the tinnitus perception by means of the THI in 16 patients treated with VSB [119]. Marino et al also analyzed the impact of VSB on existing tinnitus in 10 treated patients [120].…”
Section: Effect On Tinnitusmentioning
confidence: 99%
“…Gleichzeitig konnte in der VSB-Gruppe bei 73% der Patienten eine Verbesserung der Depressivität, welche mit dem Beck-Depressions-Inventar (BDI) evaluiert wurde, und der Stresswahrnehmung anhand des Brief Encounter Psychosocial Instrument (BEPSI) bei 55% der Patienten gezeigt werden. Eine koreanische Arbeitsgruppe zeigte eine signifikante Reduktion der Tinnituswahrnehmung anhand des THI bei 16 mit einer VSB versorgten Patienten 119 . Marino et al untersuchten ebenfalls den Einfluss der VSB Versorgung auf einen bestehenden Tinnitus bei 10 versorgten Patienten, von denen 4 Patienten einen präoperativen Tinnitus aufwiesen 120 .…”
Section: Ergebnisseunclassified
“…After this, there is a gradual recovery of balance function and this might take several days. However, further attacks may occur during this period, and this may prolong the recovery process [22]. Fluid builds up inside a part of inner ear called the labyrinth, which holds structures that help with hearing and balance.…”
Section: Balance Disordermentioning
confidence: 99%
“…Particularly beneficial in comparison to HAs is the possibility to provide large high-frequency gain [Lee et al, 2017] without need for ear canal occlusion and without feedback problems. Furthermore, a significant tinnitus reduction with VSB usage has been reported [Lee et al, 2020].…”
Section: Introductionmentioning
confidence: 97%